Epacadostat stabilizes the apo-form of IDO1 and signals a pro-tumorigenic pathway in human ovarian cancer cells - Rossini, Sofia; Ambrosino, Sara; Volpi, Claudia; Belladonna, Maria Laura; Pallotta, Maria Teresa; Panfili, Eleonora; Suvieri, Chiara; Macchiarulo, Antonio; Mondanelli, Giada; Orabona, Ciriana (Frontiers in Immunology, 2024)
The tryptophan-degrading enzyme indoleamine 2,3-dioxygenase 1 (IDO1) is a plastic immune checkpoint molecule that potently orchestrates immune responses within the tumor microenvironment (TME). As a heme-containing protein, IDO1 catalyzes the conversion of the essential amino acid tryptophan into immunoactive metabolites, called kynurenines. By depleting tryptophan and enriching the TME with kynurenines, IDO1 catalytic activity shapes an immunosuppressive TME. Accordingly, the inducible or constitutive IDO1 expression in cancer correlates with a negative prognosis for patients, representing one of the critical tumor-escape mechanisms. However, clinically trialed IDO1 catalytic inhibitors disappointed the expected anti-tumor efficacy. Interestingly, the non-enzymatic apo-form of IDO1 is still active as a transducing protein, capable of promoting an immunoregulatory phenotype in dendritic cells (DCs) as well as a pro-tumorigenic behavior in murine melanoma. Moreover, the IDO1 catalytic inhibitor epacadostat can induce a tolerogenic phenotype in plasmacytoid DCs, overcoming the catalytic inhibition of IDO1.Based on this recent evidence, IDO1 plasticity was investigated in the human ovarian cancer cell line, SKOV-3, that constitutively expresses IDO1 in a dynamic balance between the holo-and apo-protein, and thus potentially endowed with a dual function (i.e., enzymatic and non-enzymatic). Besides inhibiting the catalytic activity, epacadostat persistently stabilizes the apo-form of IDO1 protein, favoring its tyrosine-phosphorylation and promoting its association with the phosphatase SHP-2. In SKOV-3 cells, both these early molecular events activate a signaling pathway transduced by IDO1 apo-protein, which is independent of its catalytic activity and contributes to the tumorigenic phenotype of SKOV-3 cells.Overall, our findings unveiled a new mechanism of action of epacadostat on IDO1 target, repositioning the catalytic inhibitor as a stabilizer of the apo-form of IDO1, still capable of transducing a pro-